Landforms of the Balchenfjella area, the Sør Rondane, East Antarctica - Masamu Aniya (Antarctic Record, 1989)
Landforms of Balchenfjella (Balchen Mountain) and nunataks near it in the Sør Rondane, East Antarctica, were described using a geomorphological map compiled from field work and aerial photographic interpretation for Balchenfjella and aerial photographic stereograms for major nunataks. While the nunataks are in general standing out above the general surrounding ice surfaces and many of them show landforms of alpine glacier origin, Balchenfjella is characterized by landforms of areal scouring owing to continental ice-sheet glaciation and most of the area still lies below the surrounding ice surface. In this regard, Balchenfjella is found to be very unique in the Sør Rondane. Distinctive demarcation lines between the surfaces of weathered materials and fresh bedrocks found at the eastern side of the several nunataks and Balchenfjella suggest a recent lowering of the ice-sheet surface by several tens of meters. Wide covers of weathered erratics and/or tills over Balchenfjella indicate that the mountain was once covered by ice tongues spilling and closing in from surrounding sides and ablation was very extensive there. Based on the spatial distribution of weathered materials, the relative deglaciation sequence was inferred for Balchenfjella, finding that the eastern part, although higher, was most recently deglaciated. Schematic sequences of weathering, erosional and depositional processes working after deglaciation and their effects on the exposed surface were tentatively presented and the surface characteristics were listed for parts of Balchenfjella and each nunatak.